95.7k views
3 votes
Solve for z.

z − 4/9 − 1/3 = 5/9



Enter your answer as a fraction in simplest form in the box.

z =

User SIMULATAN
by
5.7k points

1 Answer

5 votes

Answer:

z = 1 1/3

Explanation:

z - 4/9 - 1/3 = 5/9

First make all the fractions have the same common denominator. Only one needs converted. Convert 1/3 into ninths like the other two.

1/3 is equal to 3/9. Since you have to multiply the bottom by 3 to get to 9, then you also have to multiply the top by 3.

Now you have

z - 4/9 - 3/9 = 5/9

Add 3/9 to each side of the equal sign.

z - 4/9 = 5/9 + 3/9 or z - 4/9 = 8/9

Add 4/9 to each side

z = 8/9 + 4/9 or z = 12/9

12/9 can be simplified to 1 3/9 or 1 1/3

User Jbarnett
by
5.3k points